2012
DOI: 10.1021/jp3088385
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Reaction Studies of Dipositive Hafnium and Hafnium Oxide Ions: Generation of the Peroxide HfO22+

Abstract: Fourier transform ion cyclotron resonance mass spectrometry was used to characterize the gas-phase reactivity of Hf dipositive ions, Hf(2+)and HfO(2+), toward several oxidants: thermodynamically facile O-atom donor N(2)O, ineffective donor CO, and intermediate donors O(2), CO(2), NO, and CH(2)O. The Hf(2+) ion exhibited electron transfer with N(2)O, O(2), NO, and CH(2)O, reflecting the high ionization energy of Hf(+). The HfO(2+) ion was produced by O-atom transfer to Hf(2+) from N(2)O, O(2), and CO(2), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…For example, some bare metal cations M + and metal-containing clusters give rise to oxygen-atom transfer (OAT) from CO 2 ; , this reaction is driven by the high oxophilicities of these species . In addition to OAT, charge transfer accompanied by coulomb explosion can occur in the thermal reactions of CO 2 with some doubly charged cations, , and a coupled oxygen–sulfur ligand-transfer mechanism is operative in the reactions of CO 2 with diatomic [MS] + (M = Y, Zr, Nb, Sc, Ti), generating COS and MO + . Further, C–X bond formation is accessible under ambient conditions by the insertion of CO 2 in an Y + –X bond (Y = metal or non-metal atoms; X = H, C, OH , ). In addition, η 2 -coordinated CO 2 on [MgOH] + undergoes C–C coupling with CH 3 Cl to produce an acetyl unit .…”
Section: Introductionmentioning
confidence: 99%
“…For example, some bare metal cations M + and metal-containing clusters give rise to oxygen-atom transfer (OAT) from CO 2 ; , this reaction is driven by the high oxophilicities of these species . In addition to OAT, charge transfer accompanied by coulomb explosion can occur in the thermal reactions of CO 2 with some doubly charged cations, , and a coupled oxygen–sulfur ligand-transfer mechanism is operative in the reactions of CO 2 with diatomic [MS] + (M = Y, Zr, Nb, Sc, Ti), generating COS and MO + . Further, C–X bond formation is accessible under ambient conditions by the insertion of CO 2 in an Y + –X bond (Y = metal or non-metal atoms; X = H, C, OH , ). In addition, η 2 -coordinated CO 2 on [MgOH] + undergoes C–C coupling with CH 3 Cl to produce an acetyl unit .…”
Section: Introductionmentioning
confidence: 99%
“…The formation of positively charged, highly energetic species such as HfO 2+ , was determined in a study by mass spectrometry using FTICR‐MS (Fourier‐transform ion cyclotron resonance mass spectrometry), combined with computational calculations at DFT−B3LYP/LANL2TZ(f) level [29] . The formation of the dimeric species (H 3 O) 3 [Hf 2 F 7 (NO 3 ) 2 (H 2 O) 2 ] ⋅ 4H 2 O 2+ , from the oxophilic monomer [HfO(H 2 O) 4 ] 2+ provided high thermodynamic stability, c.a .…”
Section: Resultsmentioning
confidence: 99%
“…The formation of positively charged, highly energetic species such as HfO 2 + , was determined in a study by mass spectrometry using FTICR-MS (Fourier-transform ion cyclotron resonance mass spectrometry), combined with computational calculations at DFTÀ B3LYP/LANL2TZ(f) level. [29] The formation of the dimeric species (H 3 O) 3 [30] and the resistance of the superhalogen anion [HfF 5 ] À to reactions with O 2 . [31] The (H 3 O) 2 [21] and HfF 4 • 3H 2 O.…”
Section: Thermodynamic Analysis Of Hf(iv)mentioning
confidence: 99%
“…[3] Pure hafnia was also evaluated in the H 2 O 2 decomposition, [4] and gas-phase studies recently demonstrated the potential of hafnium oxide cations in oxidation reactions. [5] We are not aware of any further direct catalytic application of hafnium oxide, and none of them refers to catalytic CÀC bond forming processes such as the carbonylene reaction.…”
Section: Introductionmentioning
confidence: 99%